GIS-based estimation of function mix in urban environment at neighbourhood scale - Zagorskas, Jurgis (International Conference “Environmental Engineering”, 2017)
Urban consumption is growing with every year and the studies of urban form, density, transportation, and infrastructure are becoming more popular research topics. Mixed-use development is widely recognized and discussed subject of urban sustainability. It helps to cope with energy and transportation related problems in urban environment, forms walking-friendly, economically and socially vital communities. Although mixed land use is the key planning principle of sustainable development and this term frequently appears in the urban planning strategies and literature, it is rarely elaborated upon with substantive and empirical support. Furthermore – the standard mathematical models and methods for quantifying this parameter in most cases are meant for macro-scale, e.g. comparison between cities, districts. This approach miss the human scale – the scale of walkable neighbourhood, and is not suitable to support local planning decisions and detailed measures. This study performs functional mix analysis of Klaipėda City (Lithuania) with emphasis on neighbourhood scale. The demonstrated model proves the importance of scale factor and adds another dimension to existing methods providing background for micro-scale studies of urban form.